SINDROM WEST (SPASME INFATILE) - Elvina Zuhir (Collaborative Medical Journal, 2023)
Infantile spasms are an age-appropriate epilepsy syndrome characterized by flexion, extension, and combined flexion-extension spasms that often occur simultaneously. This study may aim to identify the characteristics of infantile spasms in terms of clinical symptoms, electroencephalogram (EEG) findings, and other diagnostic tests. The development of more accurate diagnostic methods can assist in early recognition and further treatment. The results of the MRI examination showed: signs of mild cerebral atrophy were accompanied by mild myelination disorders with pathological hyper-intensity in the periventricular subcortical white matter in the pre-central / posterior frontal lobe area bilaterally, other than that other supratentorial cerebral structures did not show further abnormalities, especially in the absence of SOL, congenital anomaly, hemorrhage, cerebral dystrophy/sclerosis / malacia or other pathological intensity both supra and infra-tentorial, including in the temporal lobe and hippocampus bilaterally.